2(3x+1)+5x(x-2)=

Simple and best practice solution for 2(3x+1)+5x(x-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x+1)+5x(x-2)= equation:


Simplifying
2(3x + 1) + 5x(x + -2) = 0

Reorder the terms:
2(1 + 3x) + 5x(x + -2) = 0
(1 * 2 + 3x * 2) + 5x(x + -2) = 0
(2 + 6x) + 5x(x + -2) = 0

Reorder the terms:
2 + 6x + 5x(-2 + x) = 0
2 + 6x + (-2 * 5x + x * 5x) = 0
2 + 6x + (-10x + 5x2) = 0

Combine like terms: 6x + -10x = -4x
2 + -4x + 5x2 = 0

Solving
2 + -4x + 5x2 = 0

Solving for variable 'x'.

Begin completing the square.  Divide all terms by
5 the coefficient of the squared term: 

Divide each side by '5'.
0.4 + -0.8x + x2 = 0

Move the constant term to the right:

Add '-0.4' to each side of the equation.
0.4 + -0.8x + -0.4 + x2 = 0 + -0.4

Reorder the terms:
0.4 + -0.4 + -0.8x + x2 = 0 + -0.4

Combine like terms: 0.4 + -0.4 = 0.0
0.0 + -0.8x + x2 = 0 + -0.4
-0.8x + x2 = 0 + -0.4

Combine like terms: 0 + -0.4 = -0.4
-0.8x + x2 = -0.4

The x term is -0.8x.  Take half its coefficient (-0.4).
Square it (0.16) and add it to both sides.

Add '0.16' to each side of the equation.
-0.8x + 0.16 + x2 = -0.4 + 0.16

Reorder the terms:
0.16 + -0.8x + x2 = -0.4 + 0.16

Combine like terms: -0.4 + 0.16 = -0.24
0.16 + -0.8x + x2 = -0.24

Factor a perfect square on the left side:
(x + -0.4)(x + -0.4) = -0.24

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| A^2=a+20 | | 2x^2-15x+35=0 | | 6x+2+2-10= | | -51-5x=75-12x | | 6x+5+5x+3+8x+1=180 | | 19x=41 | | 14=6n+10 | | -(2x-3+4y)= | | -1/5(x-15)-1/9(x-9)=x-3 | | 24x-48=3x^2 | | N^3-4n=32 | | 2/5n-1=15 | | -5x-248=92-15x | | 4(3)x+2=28 | | y=x^11 | | x^3+6x^2+9x=-5 | | (14)(2)+2x+32=70 | | 4lnx-7=1 | | -4(x+4)-2=-18 | | -0.5*32x^2+24x+50=0 | | x^3+6x^2+9x=5 | | 10x+1=2x+73 | | (-1+i)-(-2-i)=0 | | -50+8x=5x+52 | | x^3+3x^2-3x=0 | | (5x+10)+7x= | | -3(x-4)+4=-4(3x-3)+6+13x | | 16m=76 | | 2x-5y=-25 | | 4(3x+8)=80 | | 6(5x+11)-9x= | | 35=-7+3n |

Equations solver categories